2012
DOI: 10.1186/1556-276x-7-392
|View full text |Cite
|
Sign up to set email alerts
|

Tunable resonance transmission modes in hybrid heterostructures based on porous silicon

Abstract: In this work, we report the experimental results and theoretical analysis of strong localization of resonance transmission modes generated by hybrid periodic/quasiperiodic heterostructures (HHs) based on porous silicon. The HHs are formed by stacking a quasiperiodic Fibonacci (FN) substructure between two distributed Bragg reflectors (DBRs). FN substructure defines the number of strong localized modes that can be tunable at any given wavelength and be unfolded when a partial periodicity condition is imposed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Periodic/quasiperiodic structures designed in the infrared have been studied [36,37], where PS structures are considered a material without optical losses. However, it has been demonstrated that light scattering by the pores and the interfaces between layers play a much more critical role than the infrared region's light absorption [38] since the extinction coefficient of crystalline silicon tends to zero [39].…”
Section: Pqs Optical Lossesmentioning
confidence: 99%
“…Periodic/quasiperiodic structures designed in the infrared have been studied [36,37], where PS structures are considered a material without optical losses. However, it has been demonstrated that light scattering by the pores and the interfaces between layers play a much more critical role than the infrared region's light absorption [38] since the extinction coefficient of crystalline silicon tends to zero [39].…”
Section: Pqs Optical Lossesmentioning
confidence: 99%
“…So far, solid-solid and solid-uid combinations have been considered through the designs of quasiperiodic structures in 1D and 2D PnCs. [27][28][29][30] Therefore, the quasiperiodic PnCs seem to be attractive candidates for overcoming the low-frequency restrictions of acoustic structures. Meanwhile, the Fibonacci sequence is considered one of the most signicant and well-known contributors in quasiperiodic PnCs structures 27,28 These quasi-periodic PnCs offer self-likeness energy spectrum, localization, as well as efficient and tunable PnBGs.…”
Section: Introductionmentioning
confidence: 99%
“…To create omnidirectional band gaps, as well as large phononic/photonic band gaps, these quasi-periodic structures could function more efficiently compared to the periodic designs. Solid–solid and solid–fluid structures have so far been created in 1D and 2D PhCs with quasi-periodic structures 65 , 68 , 70 , 71 . The available literature about the 1D or the 2D PnCs sensors does not include the Fano resonance phenomenon.…”
Section: Introductionmentioning
confidence: 99%